Bad Science: Quacks, Hacks, and Big Pharma Flacks by Ben Goldacre - Bauer, Henry (Journal of Scientific Exploration, 2013)
Ben Goldacre is a British celebrity, columnist in The Guardian, non-practicing MD, whose Bad Science sold 400,000 copies (Goldacre 2013). I had heard of him some years ago because he had committed a culpably misinformed column about the HIV/AIDS dissident Christine Maggiore (Bauer 2009). I expected only the same from his book, but was very pleasantly surprised: I urge others to read it for its sound discussions of how the media’s coverage of science is generally misleading; how misleading, too, is the way in which statistics are disseminated by drug companies and the media; and how the drug companies are not to be trusted.